Laser-powered tape placement process – simulation and optimization. (4th November 2015) - Maurer, Dennis; Mitschang, Peter
Graphical Abstract: Abstract : The laser-assisted thermoplastic tape placement process for unidirectional carbon fiber reinforced polyetheretherketon (CF PEEK) tapes was investigated. In this process, tapes are melted, laid-up on a tool, and consolidated under a roller. As an out of autoclave process, thermoplastic tape placement has high potential for aerospace manufacturing industry. To optimize laser settings for high efficiency and reproducibility, a thermal simulation was created. Process windows are calculated based on critical process temperatures. A parameter study was conducted to investigate the influence of lay-up speed and laser settings, especially laser beam height and angle of impact, on the process. For different lay-up speeds, optimum values and limits of laser settings are found to gain autoclave quality with high material output and high reproducibility. Peel specimens have been produced to verify simulated optimum parameters, which showed good agreement. Economical potential of thermoplastic tape placement was shown in a direct comparison to thermoset tape placement.